Behaviour testing in two different knockout mouse strains related to chronic inflammation and oxidative stress: Behaviour testing of CD36-/- and NRF2-/- mice - Dobri, Ana Maria; Isvoranu, Gheorghita; Enciu, Ana-Maria; Hinescu, Mihail Eugen (Cellular and Molecular Biology, 2023)
CD36, a fatty acid translocator and NRF2, a transcription factor, are two important players in inflammation and oxidative stress, including in the central nervous system. Both were associated with neurodegeneration as tilting arms of a balance: while activation of CD36 participates in neuroinflammation, activation of NRF2 seems to protect against oxidative stress and neuroinflammation. This study aimed to establish whether tilting the balance one way or the other, by knocking out either of them (NRF2-/- or CD36-/-), would show that one holds higher weight over the other in the cognitive behaviour of mice. We tested both young and old knockout animals in a long-term testing protocol (over one month), using the 8-arm radial maze,. Young NRF2-/- mice exhibited a sustained anxious-like behaviour, which was not recapitulated in old mice nor CD36 -/- mice of either age. Neither knockout strain exhibited cognitive alterations, although CD36 -/- mice showed some improvement over WT littermates. In conclusion, NRF2-/- seems to affect behaviour of mice early in life, and could be considered a vulnerability factor for neurocognition, while CD36 impact on cognitive protection of the aging brain requires more investigation.